2022
DOI: 10.3390/jof8050461
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of Mating Type of the Fungus and Sex of the Host in Studies of Fungal Infections in Humans

Abstract: This review discusses the inclusion of sex and gender variables in studies of fungal infections in humans at the pathogen, host, and antifungal trial levels. The mating type of some fungi, or perhaps more likely the absence of the other, appears to be associated with some infections. Sexual and parasexual reproduction of some fungi is an important mechanism for the development of antifungal drug resistance. Host sex or gender influences the incidence of some infections such as aspergillosis, cryptococcosis, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(143 reference statements)
0
4
0
1
Order By: Relevance
“…As a result of these two events, a paper has been published that considers sex/gender/mating type in the study of fungal infections in humans, highlighting some aspects that may be overlooked in the overall picture [ 20 ]. Sex and age of participants in antifungal trials are critical to interpret results, but researchers should already in preclinical studies report the sex of model (primary) cells or cell-culture models, and model animals [ 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these two events, a paper has been published that considers sex/gender/mating type in the study of fungal infections in humans, highlighting some aspects that may be overlooked in the overall picture [ 20 ]. Sex and age of participants in antifungal trials are critical to interpret results, but researchers should already in preclinical studies report the sex of model (primary) cells or cell-culture models, and model animals [ 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual and parasexual reproduction of some fungi is an important mechanism for the development of resistance to antifungal drugs [ 34 ]. Globalization and climate change will exacerbate the already existing challenges of fungal infections in humans; we need more multidisciplinary approaches to address them [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A gender‐wise analysis of patients with dermatophytosis showed that females (213) are slightly more predominant to tinea infections compared to males (207), which may be due to clothing variation among genders like tight fitting synthetic cloths, poor personnel hygiene, occupational history, etc. However, most of the previous studies reported that males are more susceptible to tinea infections than females 3,30,31 …”
Section: Discussionmentioning
confidence: 96%
“…However, most of the previous studies reported that males are more susceptible to tinea infections than females. 3,30,31 In respect to months, June month was at the top for the number of male and female dermatophytosis patients who visited the Department of Skin and STD with 47 male patients and 46 female patients followed by April month with 43 male patients and 38 female patients which may be due to tinea infection are susceptible to occur in warm weather condition.…”
Section: Discussionmentioning
confidence: 99%
“…Jenis kelamin laki-laki, tingkat pendidikan yang lebih tinggi, dan jumlah obat resep yang lebih tinggi dikaitkan dengan pengetahuan penyakit jamur yang lebih tinggi secara keseluruhan. Jenis kelamin berbeda dalam intensitas (yaitu, beban patogen), prevalensi (yaitu, proporsi populasi dengan penyakit), kejadian (yaitu, kasus baru), dan tingkat keparahan (yaitu, rawat inap atau perkembangan) penyakit yang disebabkan oleh jamur, virus, bakteri, dan parasit (Son et al, 2022) (Kraševec, 2022).…”
Section: Metode Penelitianunclassified